2021
DOI: 10.3390/ijerph18020745
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Rising Temperatures and the Number of Climate-Related Natural Disasters in China

Abstract: Warming has strongly influenced the quantity and variability of natural disasters around the globe. This study aims to characterize the varying patterns between rising temperatures and climate-related natural disasters in China from 1951 to 2010. We examined the overall trend in the patterns of an 11-year cycle, and climate-related natural disaster responses to periods of rising and dropping temperature. We used Morlet wavelet analysis to determine the length of a temperature cycle period, and the arc elastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…‘Climate change’ referred to any meteorological changes including both gradual changes such as increased temperatures and extreme weather events such as floods and earthquakes. Earthquakes were included as there is increasing evidence that climate change may potentially be indirectly associated with earthquake frequency: for example, it has been suggested that tectonic plate movement may be associated with the melting of glaciers [ 15 , 16 ] and rising soil temperatures [ 16 ]. Citations were imported into EndNote where one author reviewed titles, abstracts and then full texts against the inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…‘Climate change’ referred to any meteorological changes including both gradual changes such as increased temperatures and extreme weather events such as floods and earthquakes. Earthquakes were included as there is increasing evidence that climate change may potentially be indirectly associated with earthquake frequency: for example, it has been suggested that tectonic plate movement may be associated with the melting of glaciers [ 15 , 16 ] and rising soil temperatures [ 16 ]. Citations were imported into EndNote where one author reviewed titles, abstracts and then full texts against the inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…This period has not only witnessed a substantial increase in the consumption of animal products but also brought to light the imperative need for a more profound understanding of food safety and zoonotic diseases, especially in the context of global and localized disease outbreaks. Additionally, further influenced by climate change and resultant extreme weather events in China ( Li and Gu, 2020 ; Zhu and Fan, 2021 ; Cai et al., 2022 ; Zheng et al., 2023 ), these factors collectively signal the potential shifts in infectious disease dynamics. In order to address the changing health concerns in this important field, our research used meta-analysis to determine the effects of these environmental and public health changes on T. gondii seroprevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Climate‐related disasters significantly affect the populations that experience them, as well as the natural environment where they occur [5], causing a substantial impact on physical health. They are associated with various types of injuries, respiratory diseases such as asthma, dermatological diseases [6], or altering the spread of communicable diseases [7].…”
Section: Introductionmentioning
confidence: 99%